Improvement of a Device for Softening Drinking Water by Electromagnetic Method (Texas Journal of Engineering and Technology, 2025)
This research focuses on the improvement of a device for softening drinking water using an electromagnetic method. The existing methods of water softening, such as ion exchange and reverse osmosis, are often expensive and energy-intensive. Electromagnetic water softening presents a promising alternative, as it is a non-chemical, environmentally friendly approach. The study investigates the effectiveness of different electromagnetic field parameters, including frequency, intensity, and exposure time, on the reduction of hardness ions in water. A prototype device is designed and tested using various water samples with different levels of hardness. The results are analyzed to determine the optimal electromagnetic field parameters for achieving significant water softening. The research also explores the potential mechanisms of electromagnetic water softening, including the disruption of calcium and magnesium ion bonds, the formation of stable micro-crystals, and the reduction of scaling potential. The findings of this study contribute to the development of a more efficient and sustainable water softening technology